Pneumonia in a Paso-Fino mare - MacNeill, Amy L (Veterinary clinical pathology, 2003)
A 5-year-old Paso-Fino mare was presented for severe respiratory distress. The mare had foaled 2 months prior to presentation. The horse was in poor body condition with a dull hair coat. A mild fever was noted during physical examination and increased bronchovesicular sounds were auscultated. Thoracic radiographs showed an interstitial pattern and an alveolar infiltrate with distinct air bronchograms. Moderate purulent inflammation with increased mucus was observed in tracheal wash fluid, but no infectious agents were identified. A bronchoalveolar lavage (BAL) contained a large amount of mucus and reactive mononuclear phagocytes with variable numbers of intracellular fungal organisms morphologically consistent with Pneumocystis carinii. The mare had undetectable levels of immunoglobulin M (IgM) and decreased IgG levels in the serum. Immunophenotyping revealed decreased expression of major histocompatibility complex (MHC) class II molecules. Moderate to marked hyperplasia of type II epithelial cells was present throughout histologic sections of lung, but the fungal organisms were not observed. A culture system has not been developed for diagnosis of P carinii infection. Instead, diagnosis of P carinii pneumonia is achieved by microscopic identification of characteristic morphologic features of the pathogen. Cytologic examination of BAL fluid is the preferred method used to diagnose human infection with P carinii. In humans, the diagnostic sensitivity of cytology is significantly higher than the sensitivity of histopathologic examination of lung biopsies. The difference in sensitivity between BAL cytology and lung histopathology may also apply to the diagnosis of P carinii pneumonia in horses